2010
DOI: 10.1016/j.otsr.2009.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Tibial segmental bone defect reconstruction by Ilizarov type bone transport in an induced membrane

Abstract: The management of combined loss of skin coverage and bone substance in the lower third of the leg is problematic. A recommended sequential strategy associates removal of infected tissue and coverage followed by treatment of the bone defect. We report a technique without microsurgery, using Masquelet's induced membrane technique to manage the bone loss, associated to bone transport and coverage by a fasciocutaneous flap with distal pedicle. In a patient presenting with a 10 cm defect with bone exposure, this 2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…Our results are encouraging and comparable to other studies which used the same technique of transport over induced membrane in management of infected nonunion of the tibia [21][22]. In contrary to other studies, our protocol highlights the role of using NPWT following debridement of infected nonunion and the use of structural cement-spacer support in the latency period before embarking on tissue reconstruction.…”
Section: Discussionsupporting
confidence: 81%
“…Our results are encouraging and comparable to other studies which used the same technique of transport over induced membrane in management of infected nonunion of the tibia [21][22]. In contrary to other studies, our protocol highlights the role of using NPWT following debridement of infected nonunion and the use of structural cement-spacer support in the latency period before embarking on tissue reconstruction.…”
Section: Discussionsupporting
confidence: 81%
“…Group B: the mean consolidation time was 323 days (range 187-559 days). Soft tissue interposition at the docking site was seen three times before surgical docking [11,18,24] (Fig. 2), and a false aneurism of the peroneal artery was seen after one of the surgical docking site procedures (this was treated by embolisation).…”
Section: Resultsmentioning
confidence: 99%
“…Confirming data obtained in sheep (Viateau et al ., ) and rabbits (Viateau et al ., ), the present results indicate that the membrane consists of a dense collagen network organized parallel to the PMMA. In humans, an induced membrane has been shown to be calcified even before grafting (Uzel et al ., ), which may indicate that the membrane is able to promote both graft osteointegration and mineralization. Confirming this hypothesis, the membranes induced in the model used in the present study showed islets of calcification by the third week after PMMA insertion.…”
Section: Discussionmentioning
confidence: 97%